1999
DOI: 10.1074/jbc.274.35.24567
|View full text |Cite
|
Sign up to set email alerts
|

Skp, a Molecular Chaperone of Gram-negative Bacteria, Is Required for the Formation of Soluble Periplasmic Intermediates of Outer Membrane Proteins

Abstract: Using a cross-linking approach, we have analyzed the function of Skp, a presumed molecular chaperone of the periplasmic space of Escherichia coli, during the biogenesis of an outer membrane protein (OmpA). Following its transmembrane translocation, OmpA interacts with Skp in close vicinity to the plasma membrane. In vitro, Skp was also found to bind strongly and specifically to pOmpA nascent chains after their release from the ribosome suggesting the ability of Skp to recognize early folding intermediates of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(178 citation statements)
references
References 43 publications
(48 reference statements)
6
164
0
6
Order By: Relevance
“…Both proteins may act in either the same or, as genetic evidence suggests (22), in a parallel folding pathway. Skp has been shown to interact with early OMP folding intermediates at the periplasmic side of the inner membrane and to be required for the release and the maintenance of soluble periplasmic intermediates (23,24). Whether Skp also acts in late, outer membrane-associated steps of OMP maturation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins may act in either the same or, as genetic evidence suggests (22), in a parallel folding pathway. Skp has been shown to interact with early OMP folding intermediates at the periplasmic side of the inner membrane and to be required for the release and the maintenance of soluble periplasmic intermediates (23,24). Whether Skp also acts in late, outer membrane-associated steps of OMP maturation is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Skp also binds to and inserts into monolayers of negatively charged lipids [51]. Skp binds to the NH 2 -terminal part of OmpA and is required for the release of OmpA into the periplasm [52,53]. Skp does not bind to folded OmpA [46], suggesting that Skp recognizes nonnative structures of OMPs.…”
Section: Role Of Periplasmic Proteins (Chaperones Isomerases)mentioning
confidence: 99%
“…One model is that periplasmic chaperones like Skp maintain the ␤-barrel domain of OMPs in an unfolded state to facilitate their insertion in the membrane. However, some studies have suggested that Skp recognizes a conformational motif in its substrates rather than extended, unfolded polypeptides (7,19), implying that substrate proteins must be at least partially folded when bound by Skp. To directly address this issue, heteronuclear NMR experiments were used to monitor the folding state of the ␤-barrel domain of OmpA (amino acids 1-177; OmpA 177 ) in complex with Skp.…”
Section: Skp Prevents the Aggregation Of Ompa By Forming A Stable Commentioning
confidence: 99%
“…In vivo, Skp has been shown to be important for the folding and insertion of several OMPs (5,7,19,22). These OMPs share the signature ␤-barrel structure as their integral membrane domain.…”
Section: Skp Prevents the Aggregation Of Ompa By Forming A Stable Commentioning
confidence: 99%